Resonant inverter design for induction heating / Ferry Syafrizal Sabir Husin - Sabir Husin, Ferry Syafrizal (1995)
This thesis presents a hardware development of a Resonant Inverter designed for low power Induction Heating. This Resonant Inverter technique is introduced to minimize the number of power switching devices used in the system. The performance at 50 kHz and the dc to ac power MOSFET inverter in generating high frequency flux to heat stainless steel vessels are investigated. In this design, power MOSFET ( IRF840 ) with rating 500V / 8A has been used as resonant inverter with operating frequencies up to 50 kHz. The heating coil used a few layers designed as concentric flat coils connected together in away to produce maximum flux to be penetrated in the magnetic material vessel.